Reading comprehension in aphasia: the relationship between linguistic performance, personal perspective, and preferences. Issue 5 (4th May 2023) - Webster, Janet; Morris, Julie; Howard, David
ABSTRACT: Background: Reading is an important everyday activity. Extensive individual variability exists in both typical readers and readers with aphasia in their reading ability, preferences, and practice. Although reading comprehension difficulties in people with aphasia are typically assessed at single word, sentence, and text level, there is limited information about how performance at these levels corresponds to their enjoyment and practice of reading. Aims: This study aimed to improve our understanding of reading in people with aphasia by examining: 1) the relationship between performance on assessments of word, sentence, and paragraph comprehension; 2) the relationship between reported reading difficulty, feelings about reading, and reading activity; and 3) the relationship between reading comprehension scores and personal perception of reading. Methods & Procedures: Participants included 74 adults with a single symptomatic stroke resulting in aphasia; they did not have to report or present with reading difficulties. Participants completed the Comprehensive Assessment of Reading in Aphasia (CARA). Statistical analysis used Spearman correlations to investigate the relationship between measures. Illustrative case studies provided evidence of individual variability. Outcomes & Results: Significant positive correlations were found between comprehension accuracy in single word and sentence, single word and paragraph, and sentence and paragraph assessments. There were also significant positive correlations among reported reading difficulty, feelings about reading, and reading activity. There were no significant correlations between reading comprehension scores and personal perception of reading. Conclusions: There is no straightforward relationship between reading comprehension difficulties and individual perception of reading. This emphasises the importance of considering both when discussing and agreeing goals, selecting a treatment approach, and evaluating the outcome of intervention.